Hệ tầng dưỡng động trong môi trường tương quan với các hệ tầng tuổi Paleozoi vùng duyên hải đông bắc bắc bộ - Phương, Tạ Hòa; Hoàn, Nguyễn Văn; Phương, Phạm Nguyên (VNU Journal of Science: Natural Sciences and Technology, 2004)
A supplementary collection of Brachiopod and Pelecypod fossils has recently been gathered from the Duong Dong formation in Kinh Mon area, Hai Duong province which includes  Carinatina cf.  arimaspa (Eichw.),  Desquamatia sp.,  Atrypa sp.,  Retichonetes sp., Bacbochonetes ja n v ie r i  Rach.,  Perichonetes mutabilis Xu,  Leptostrophia sp. The above- mentioned fossils are approximately of Praga-Emsi age (Early Devonian). Through the analysis of substantial composition, rock facies, age and the interrelation of the Duong Dong formation (Dị.  clđ) with the Kien An (S;;.,  kn) and Do Son (Dds) formations, one question has been put forward by the authors whether the sedimentary formations with similar composition but different facies (specifically the Duong Dong and Do Son formations), which are simultaneously intercepted in the upper by one formation with different composition (Trang Kenh formation), can be considered as  2 independent formations. The authors are of the opinion that the above formations are synonymous, and the name "Do Son formation" shoucl be preferentially retained.